Young Migrants and Plurilingualism in Schools : A Comparative Study of Language Diversity within Education Systems in France and Aotearoa New Zealand - Smythe, Fiona, (Comparative and International Education: Francophonies ;, 2025)
In many parts of the world, there is a growing interest in how existing linguistic knowledge is involved in the acquisition of further languages; in particular how learning the language of schooling can be improved through inclusion of students' home languages. This theme gathers around it a rich international network of multilingual researchers interested in promoting the benefits of bilingual and plurilingual education, the recognition of linguistic and cultural diversity in schools, and strategies for supporting young migrants to succeed in schools. Young Migrants and Plurilingualism in Schools: A Comparative Study of Language Diversity within Education Systems in France and Aotearoa, New Zealand presents findings from the author's Ph.D. study carried out during 2017-2019 with young migrants and their teachers in France and New Zealand. These findings provide evidence for plurilingual learning spaces as improving student participation, interaction, sense of wellbeing and social cohesion-all elements of democratic coexistence in culturally and linguistically diverse societies.